Bulk components, and concentration and stable carbon isotopic composition of diacids and related compounds in PM2.5 from underground coal fire field in 2018 in Inner Mongolia, North China - Xu, Zhanjie; Zhao, Xiaomai; Sun, Ruoyu; Pavuluri, Chandra Mouli (PANGAEA, 2022)
To understand the characteristics of chemical components and diacids, oxoacids, and α-dicarbonyls in atmospheric aerosols at underground coal fire environment, we collected fine aerosols (PM2.5) in September, October, and December of 2018 from Wuhai, Inner Mongolia, North China, where the underground coal fire occurs severely. The datasets include the concentrations of PM2.5, and carbonaceous components (i.e., total carbon, TC; organic carbon, OC; Elemental carbon, EC; water-soluble OC, WSOC), inorganic ions, and diacids, oxoacids, and α-dicarbonyls and stable carbon isotope ratios of TC and diacids, oxoacids, and α-dicarbonyls in the PM2.5 samples (n =13). OC and EC were measured using OC/EC analyzer (Sunset Laboratory Inc., USA), based on thermal light reflectance following the IMPROVE protocol of the protective visual environment. The concentration of WSOC was measured using a TOC analyzer (TOC-L, 5000A, Shimadzu, Japan). Inorganic ions were measured using ion chromatography (Thermo Fisher, ICS 5000+). Diacids and related compounds were measured using a capillary gas chromatography (GC; Agilent 7890B). δ13C (‰; PDB) of TC was determined using an elemental analyzer (EA, Flash 2000HT) coupled with a stable isotope ratio mass spectrometer (IRMS, 253Plus), while the compound-specific δ13C (‰; PDB) of diacids, oxoacids, and α-dicarbonyls were determined using the GC-IRMS (Thermo Fisher, Mat253).
Keywords: carbon isotope ratio (δ13C); Coalfield spontaneous combustion; Dicarboxylic acids; fine aerosols; Inner Mongolia